Total cholesterol, arterial stiffness, and systolic blood pressure: a mediation analysis - Haojia Chen (Nature Portfolio, 2021)
Abstract On the basis of 45,092 participants (mean age of 54.04 ± 13.09 years) from the Kailuan study, this study was performed to explore the relationships among total cholesterol (TC), brachial-ankle pulse wave velocity (BaPWV), and systolic blood pressure (SBP) and quantify their separate effects. The correlations among TC, SBP, and BaPWV were analyzed using multivariate linear regression models. Mediation analysis was performed to determine whether the effect of TC on SBP can be explained by arterial stiffness. Multivariate linear regression analysis showed that for every one standard deviation increase in TC and BaPWV, SBP increased by 0.33 mmHg and 0.044 mmHg, respectively; for every one standard deviation increase in TC, BaPWV increased by 5.34 cm/s. Mediation analysis showed that the TC-induced SBP elevation was mediated by arterial stiffness in more than half of the whole cohort (indirect effect, 0.73; percent mediated, 54.5%). Furthermore, the TC-induced SBP elevation was mediated by arterial stiffness in less than half of the males (indirect effect, 0.70; percent mediated, 47.9%); however, the results were not statistically significant in females. In conclusion, TC and BaPWV are positively correlated with SBP, whereas TC is positively correlated with BaPWV. Almost half of the increase in SBP contributed to TC is mediated by arterial stiffness.